Intersubjectivity and a practical intersubjective ethics of translation - Jun, Tang (2004)
This essay suggests that the intersubjectivity in translation should be given priority because different stages of the translation activity have different subjects, and presents a practical intersubjective ethics of translation based on an interpretation of the intersubjective relations connected with translation activities in a perspective of game theory in the hope that it can equip us with better explanations of the translator’s calculations or considerations in the professional practice.